A Retrospective Analysis of Patients with Short Stature in Eastern China between 2013 and 2019. (21st April 2021) - Zhao, Qianqian; Zhang, Mei; Chu, Yuntian; Sun, Hailing; Pan, Hui; Ban, Bo
Abstract : Objective . To identify the aetiology of growth and development diseases and assess the long-term effectiveness of recombinant human growth hormone (rhGH) therapy in a real-life clinical setting and provide better guidance in clinical strategy and decision making. Methods . This retrospective study included 1145 children and adolescents with short stature admitted to the Department of Endocrinology, Affiliated Hospital of Jining Medical University, from January 2013 to December 2019, of whom 484 received rhGH treatment. The related anthropometrics and laboratory examinations were assessed in all participants. Results . A total of 1145 children and adolescents with short stature aged 10.5 ± 3.3 years, including 740 boys and 405 girls, were analysed in this study. The number of children and adolescents with short stature gradually increased per year from 2013 to 2019. The mean pretreatment height standard deviation score (SDS) and insulin-like growth factor-1 SDS were − 2.93 ± 1.05 and -1.01 (-1.83–0.16), respectively. The majority of the children (658, 57.47%) were prepubescent. In total, 484 subjects aged 10.6 ± 3.2 years received rhGH and were followed up, and among them, 292 children were treated for more than one year. As the treatment time increased, the children's height SDS gradually increased, and most of them attained a height SDS within the normal range. The mean height SDS in children who were treated for more than one year was − 3.0 ± 1.0 at baseline and gradually increased to − 0.8 ± 0.3 by year 6. The results were consistent across subgroups of different aetiologies of short stature. Conclusions . Increasing attention has been given to the height of children during the period of 2013–2019 in eastern China. The present findings indicate that children with short stature need to be referred to a specialist centre to diagnose the cause of growth failure and that short children receiving rhGH therapy show a significant increase in height over time.